Monensin and nigericin prevent the inhibition of host translation by poliovirus, without affecting p220 cleavage. - Irurzun, A (1995)
Addition of monensin or nigericin after poliovirus entry into HeLa cells prevents the inhibition of host protein synthesis by poliovirus. The infected cells continue to synthesize cellular proteins at control levels for at least 8 h after infection in the presence of the ionophore. Cleavage of p220 (gamma subunit of eukaryotic initiation factor 4 [eIF-4 gamma]), a component of the translation initiation factor eIF-4F, occurs to the same extent in poliovirus-infected cells whether or not they are treated with monensin. Two hours after infection there is no detectable intact p220, but the cells continue to translate cellular mRNAs for several hours at levels similar to those in uninfected cells. Nigericin or monensin prevented the arrest of host translation at all the multiplicities of poliovirus infection tested. At high multiplicities of infection, an unprecedented situation was found: cells synthesized poliovirus and cellular proteins simultaneously. Superinfection of vesicular stomatitis virus-infected HeLa cells with poliovirus led to a profound inhibition of vesicular stomatitis virus protein synthesis, while nigericin partially prevented this blockade. Drastic inhibition of translation also took place in influenza virus-infected Vero cells treated with nigericin and infected with poliovirus. These findings suggest that the translation of newly synthesized mRNAs is dependent on the integrity of p220, while ongoing cellular protein synthesis does not require an intact p220. The target of ionophore action during the poliovirus life cycle was also investigated. Addition of nigericin at any time postinfection profoundly blocked the synthesis of virus RNA, whereas viral protein synthesis was not affected if nigericin was added at 4 h postinfection. These results agree well with previous findings indicating that inhibitors of phospholipid synthesis or vesicular traffic interfere with poliovirus genome replication. Therefore, the action of nigericin on the vesicular system may affect poliovirus RNA synthesis. In conclusion, monensin and nigericin are potent inhibitors of poliovirus genome replication that prevent the shutoff of host translation by poliovirus while still permitting cleavage of p220.